The return of YHWH : the tension between deliverance and repentance in Isaiah 40-55 - Scheuer, Blaženka. (Berlin ; New York : Walter de Gruyter, 2008)
The theology of Isaiah 40-55 has two seemingly contradictory aspects: the tension between the consolatory message of deliverance, and the harsh tone of accusation and the call to repentance. This study argues that such tension does not necessarily disclose a different authorship, but that it expresses the basic nature of the relationship between YHWH and the Israelites, in which the actions of YHWH and the actions of the people stand in a relationship of interdependence. Such interdependence is essential for the re-establishment and the continued existence of the relationship between YHWH and.
Introduction -- The subject of this investigation -- The historical context -- Redaction -- Procedure -- Definition of concepts -- The history of research -- The call to repentance -- Sin and repentance in Isaiah 40-50 -- Studies that refer to the "sins of the past" -- Studies that refer to the "sins of the present" -- Sin, repentance and transformation -- Accusations against the Israelites -- Isaiah 43:22-28 -- Isaiah 46:8-13 -- Isaiah 46:8-11 -- Isaiah 46:12-13 -- Isaiah 48:1-11 -- Isaiah 50:1-3 -- The calls to repentance -- Isaiah 44:21-22 -- Isaiah 55:6-7 -- Repentance in Isaiah 55 -- Repentance and deliverance in Isaiah 55 -- The function of transformation -- The idol-worshippers -- Idol-fabrication texts -- Isaiah 40:19-20 -- Isaiah 41:6-7 -- Isaiah 44:9-20 -- Isaiah 46:6-7 -- The charges against the nations -- The idol-worshippers : the nations or the Israelites? -- Jeremiah and Ezekiel -- Jeremiah -- The calls to repentance -- Jeremiah 3 -- The transformation texts -- Ezekiel -- The calls to repentance -- The transformation texts -- Jeremiah, Ezekiel and Deutero-Isaiah -- Deliverance and repentance -- The concept of sin -- The explicit formulations -- The implicit statements -- The concept of repentance -- The concept of deliverance -- The relationship between deliverance and repentance -- The return of YHWH -- The tension as a theological challenge.
Includes bibliographical references (pages 149-164).
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Repentance; Repentir; RELIGION -- Biblical Studies -- Prophets; Repentance; Criticism, interpretation, etc